Pharmacokinetic modeling of R and S‐Methadone and their metabolites to study the effects of various covariates in post‐operative children. (26th August 2021) - Aruldhas, Blessed W.; Quinney, Sara K.; Overholser, Brian R.; Heathman, Michael A.; Masters, Andrea R.; Ly, Reynold C.; Gao, Hongyu; Packiasabapathy, Senthil; Sadhasivam, Senthilkumar
Abstract: Methadone is a synthetic opioid used as an analgesic and for the treatment of opioid abuse disorder. The analgesic dose in the pediatric population is not well‐defined. The pharmacokinetics (PKs) of methadone is highly variable due to the variability in alpha‐1 acid glycoprotein (AAG) and genotypic differences in drug‐metabolizing enzymes. Additionally, the R and S enantiomers of methadone have unique PK and pharmacodynamic properties. This study aims to describe the PKs of R and S methadone and its metabolite 2‐ethylidene‐1, 5‐dimethyl‐3, 3‐diphenylpyrrolidine (EDDP) in pediatric surgical patients and to identify sources of inter‐ and intra‐individual variability. Children aged 8–17.9 years undergoing orthopedic surgeries received intravenous methadone 0.1 mg/kg intra‐operatively followed by oral methadone 0.1 mg/kg postoperatively every 12 h. Pharmacokinetics of R and S methadone and EDDP were determined using liquid chromatography tandem mass spectrometry assays and the data were modeled using nonlinear mixed‐effects modeling in NONMEM. R and S methadone PKs were well‐described by two‐compartment disposition models with first‐order absorption and elimination. EDDP metabolites were described by one compartment disposition models with first order elimination. Clearance of both R and S methadone were allometrically scaled by bodyweight. CYP2B6 phenotype was a determinant of the clearance of both the enantiomers in an additive gene model. The intronic CYP3A4 single‐nucleotide polymorphism (SNP) rs2246709 was associated with decreased clearance of R and S methadone. Concentrations of AAG and the SNP of AAG rs17650 independently increased the volume of distribution of both the enantiomers. The knowledge of these important covariates will aid in the optimal dosing of methadone in children.